(untitled) (Marketing Journal, 2025)
The article describes the modern methodological approaches of establishing econometric provision of food and general catering services development. In particular, a complex system of indicators for complex economic analysis of the activities of public accommodation and catering enterprises, a scenario for classifying the analysis of the activities of enterprises by criteria, and economic statistical a nalysis of development are presented.